PREDICATIVE EVALUATIVE NOMINATION: LINGUO-COGNITIVE ASPECT - Cherkas , Nataliia (Collection of scientific papers «ΛΌГOΣ», 2023)
The basis for the interpretation of the belles-lettres text is the model of the situation, which presents all the information for an adequate understanding of the text, the discourse and its context. Knowledge of the language, of the world, knowledge of attitudes, ideas, evaluations of the author, as well as judgment, ethical, aesthetic, emotional evaluations of the recipient are used in the process of interpretation. The recipient’s previous experience should be used to create a model of the new situation. A cognitive structure such as the global (vertical) context acquires special importance in the perception of the belles-lettres text. To understand the text, you need to imagine the problem reproduced in it. This is its global content, the macrostructure of the text, its theme. The theme consists of several subthemes presenting unity and interaction. The theme of the text is the center that connects the subthemes. The so-called strong positions of the text contribute to the definition of the theme ˗ the title, beginning and end. The so-called topical or nominative chains, which are also called thematic words of the text, belong to the most important semantic landmarks of the text. They connect the text with its title, determine the internal coherence of the text, contribute to its semantic unfolding.